Cerebral blood volume Alberta Stroke Program Early Computed Tomography Score predicts intracranial hemorrhage after thrombectomy in patients with acute ischemic stroke in an extended time window. (March 2022) - Cao, Yue-Zhou; Zhao, Lin-Bo; Jia, Zhen-Yu; Liu, Qiang-Hui; Xu, Xiao-Quan; Shi, Hai-Bin; Liu, Sheng
Background: Higher baseline Alberta Stroke Program Early Computed Tomography Score (ASPECTS) was associated with a lower probability of hemorrhagic transformation in patients with acute ischemic stroke (AIS). Purpose: To investigate the predictive value of cerebral blood volume (CBV)-ASPECTS of intracranial hemorrhage (ICH) in AIS treated with thrombectomy selected by computed tomographic perfusion (CTP) in an extended time window. Material and Methods: A total of 91 consecutive patients with AIS with large vessel occlusion in the anterior circulation after thrombectomy in an extended time window were enrolled between January 2018 and September 2019. ICH was diagnosed according to Heidelberg Bleeding Classification. CBV-ASPECTS was assessed by evaluating each ASPECTS region for relatively low CBV value compared with the mirror region in the contralateral hemisphere. Demographic characteristics, clinical data, CBV-ASPECTS, and procedure process and results were compared between patients with ICH and those without. Results: ICH occurred in 31/91 (34.1%) patients with AIS. Symptomatic ICH (sICH) was observed in 4 (4.4%) patients, while asymptomatic ICH (aICH) was seen in 27 (29.7%). In univariate analysis, both ICH and aICH were associated with high admission NIHSS score ( P <0.001 and P <0.001, respectively), more passes of retriever ( P  = 0.007 and P  = 0.019, respectively), low NCCT-ASPECTS ( P  = 0.013 and P  = 0.034, respectively), and low CBV-ASPECTS ( P  < 0.001 and P  < 0.001, respectively). After multivariable analysis, low CBV-ASPECTS remained an independent predictor of ICH (odds ratio [OR] 0.521, 95% confidence interval [CI] 0.371–0.732, P  < 0.001) and aICH (OR 0.532, 95% CI 0.376–0.752, P  < 0.001), respectively. Conclusion: Low CBV-ASPECTS independently predicts ICH in patients with AIS treated with thrombectomy selected by CTP in an extended time window.